Coproduction of 5-Aminovalerate and δ-Valerolactam for the Synthesis of Nylon 5 From L-Lysine in Escherichia coli - Cheng, Jie; Tu, Wenying; Luo, Zhou; Liang, Li; Gou, Xinghua; Wang, Xinhui; Liu, Chao; Zhang, Guoqiang (Frontiers in Bioengineering and Biotechnology, 2021)
The compounds 5-aminovalerate and δ-valerolactam are important building blocks that can be used to synthesize bioplastics. The production of 5-aminovalerate and δ-valerolactam in microorganisms provides an ideal source that reduces the cost. To achieve efficient biobased co-production of 5-aminovalerate and δ-valerolactam in Escherichia coli, a single biotransformation step from L-lysine was constructed. Firstly, an equilibrium mixture was formed by L-lysine α-oxidase RaiP from Scomber japonicas. In addition, by adjusting the pH and H2O2 concentration, the titers of 5-aminovalerate and δ-valerolactam reached 10.24 g/L and 1.82 g/L from 40 g/L L-lysine HCl at pH 5.0 and 10 mM H2O2, respectively. With the optimized pH value, the δ-valerolactam titer was improved to 6.88 g/L at pH 9.0 with a molar yield of 0.35 mol/mol lysine. The ratio of 5AVA and δ-valerolactam was obviously affected by pH value. The ratio of 5AVA and δ-valerolactam could be obtained in the range of 5.63:1-0.58:1 at pH 5.0-9.0 from the equilibrium mixture. As a result, the simultaneous synthesis of 5-aminovalerate and δ-valerolactam from L-lysine in Escherichia coli is highly promising. To our knowledge, this result constitutes the highest δ-valerolactam titer reported by biological methods. In summary, a commercially implied bioprocess developed for the coproduction of 5-aminovalerate and δ-valerolactam using engineered Escherichia coli.